Isolation and Identification of Indigenous Polypropylene-Degrading Bacteria Isolated From Bestari Landfill of Probolinggo - Yuliana, Shinta; Wijayanti, Chandra; Qodriyah, Nur Romadhona Lailatul; Sanjaya, Eli Hendrik; Wahab, Roswanira Abdul; Susanti, Evi (Jurnal Kimia Fullerene, 2025)
The Bestari Landfill of Probolinggo City collects a variety of plastics waste, most of it already in a degraded state. It is estimated to be potential habitat for polypropylene-degrading bacteria. Previous NGS studies identified 2,400 species of bacteria, but did not reveal their physiological and functional characteristics. This study aims to identify PP-degrading bacteria using 16S rRNA analysis. Isolation is carried out by the Enrichment method on Mineral Salt Media (MSM) containing PP granules. The research stages included sampling, isolation, and screening of bacteria for the most effective degrading agents. Six isolates of polypropylene-degrading bacteria were discovered at the Bestari Landfill of Probolinggo City, including B1UM1, B1UM2, B1UM3, B2UM1, B2UM2, and B2UM3. After 15 days of incubation, potential isolates B1UM1, B1UM2, and B2UM1 showed the highest polymer reduction of 8.25%, 7.15%, and 6.25%. Gram staining results showed that isolate B1UM1 was coccus and a Gram-positive bacterium, while isolates B1UM2 and B2UM1 were basil and Gram-positive. Genotypic identification through 16S rRNA sequence analysis showed that isolate B1UM1 had 100.0% similarity with Staphylococcus haemolyticus, BIUM2 had a 100% similarity to Bacillus cereus, and B2UM1 had a 99% had a similarity to Bacillus sp.